ANALISIS KEMAMPUAN SPASIAL SISWA BERKEMAMPUAN MATEMATIKA TINGGI DALAM MENYELESAIKAN MASALAH GEOMETRI BANGUN RUANG SISI DATAR - Silalahi, Lidia Christine; Rizal, Muh.; Sugita, Gandung (Aksioma, 2020)
Abstract: This research aims to describe the spatial ability of grade VIII students SMP Kristen GPID Palu in Solving Flat Geometry Problems in Flat-Side Space Based on High. The type of this research is a case study research with a qualitative approach. The subject that use in this research are the students who have high mathematical abilities (ST). The research subjects were given geometry tests to construct a flat side space problem I and then interviewed. To test the credibility of the data, time triangulation was carried out by giving geometry tests to construct the flat side space of problem II and conducting interviews. Based on the results of the analysis it was found that in spatial perception ability, ST were able to determine unit cubes located in the horizontal position and vertical position in the cube stack after being manipulated. Besides that for mental rotation ability, ST is able to rotate the position of the cube and imagine the rotation of the cube correctly. ST determines the change of the cube after being rotated 900 counterclockwise by imagining rotating the cube right to the left. As well as in spatial visualization ability, ST is able to determine the change of cubes into different forms and recognize changes in position of the elements of the cube. ST is able to determine the location of the triangle, circle, and quadrilateral image in the cube network that shows the inside of the cube after being rotated twice.